Innovation in Balaghah Learning through the Development of an Infographic-Based E-Module (A Theoretical Review) - Rofiazka Fahmi Huda; Neldi Harianto; Salman Jufri; Warissuddin Soleh (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This study aims to theoretically examine the innovation of balaghah learning through the development of infographic-based e-modules as an effort to enhance the effectiveness and attractiveness of the teaching and learning process. Balaghah, as one of the important branches of Arabic linguistics, is often considered difficult for students to understand due to its abstract nature and dense concepts. Therefore, it is necessary to innovate learning media that can visualize balaghah concepts in a simple, systematic, and interactive manner. Infographic-based e-modules are considered relevant because they combine the power of visuals with concise conceptual explanations, thus facilitating comprehension and retention of the material. This article discusses the theoretical foundation of e-module development, the principles of effective infographic design, and its implications for balaghah learning. The study emphasizes that the use of infographics in e-modules has the potential to increase learning motivation, strengthen conceptual understanding, and support more efficient independent learning. These theoretical findings are expected to serve as a reference for Arabic language learning media developers and educators to integrate visual technology into balaghah instruction.